Pre-natal and post-natal anxiety in relation to pre-pregnancy obesity: a cohort study on Iranian pregnant women. - Azizeh Farshbaf-Khalili; Sakineh Hajebrahimi; Alireza Ostadrahimi; Jamileh Malakouti; Hanieh Salehi-Pourmehr (Babol University of Medical Sciences, 2020)
Background: To determine the association between pre-conception obesity and screening results of pre-natal and post-natal anxiety in women that referred to the health centers of Tabriz, Iran. Methods: 62 obese (class 2-3) and 245 normal-weight women were enrolled in the first trimester of pregnancy through the cohort study and followed-up 1 year after childbirth from December 2012 to January 2016. The Beck anxiety inventory scale (BAI-II) was completed in five time points: the first, second, third trimester of pregnancy, 6-8 weeks and 12 months after childbirth. Chi-square, Fisher's exact tests, Independent t-test, MannWhitney, and multivariate logistic regression adjusted for confounders were used for data analysis. Statistically significant was considered as p<0.05. Results: The rate of moderate to severe anxiety in 1st, 2nd, 3rd trimesters of gestation, 6-8 weeks and 12 months after birth was 8.6%, 10%, 12.6%, 7.8%, 6.5% in normal weight women versus 18%, 17.9%, 19.2%, 12.5%, 19.4% in obese class II women, respectively. The odds of anxiety in the first trimester of pregnancy for class 2-3 obesity was 2.72-fold greater than normal weight group [adjusted odds ratio (aOR) 2.72, 95% confidence interval (CI) 1.14-6.47; p=0.023]. This odd was 3.30- fold (aOR 3.30, 95%CI 1.13-9.60; p=0.045) for 1 year after birth. Conclusion: Obesity remained associated with positive screening for anxiety in the first trimester of pregnancy and one year after birth. Obese women more likely require special medical care during their pregnancy due to its impacts on mood.